Un'applicazione di indicatori, basata sulla ricerca, per misurare la qualità dell'istruzione - Jaap Scheerens; Jan van Ravens; Hans Luyten (LED Edizioni Universitarie, 2011)
A Research Based Application of Indicators to Measure Educational Quality This article considers perceptions of educational quality and the use of educational indicators to measure quality. Use of quality indicators is illustrated on the functioning of primary and secondary education in the Netherlands. The well-known systems model, which defines education as a production process that is supported by certain inputs and leads to specific outcomes, is used as a basic framework to present more specific facets of educational quality. These are: productivity, effectiveness, efficiency, equity and responsiveness to the external context. Elements of the systems model are also seen as the basis for defining input, process, outcome and context indicators. In the application to Dutch primary and secondary education the emphasis is on the use of outcome indicators. In this application achievement and attainment outcome indicators are analyzed together. The Netherlands has been scoring consistently high on international comparative assessments in reading, mathematics and science, but shows attainment level that are only slightly above the mean of OECD countries. This pattern of achievement and attainment indicators is seen as indicative of the selectivity of the Dutch education system, which in its turn can be explained by the high level of stratification. It is concluded that there is room for improvement in the realm of educational attainment even more than is the case for achievement, which is the focus of current educational policy.